2020
DOI: 10.3390/nu12103156
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Intake Patterns and Inadequate Protein Intake in Older Adults from Four Countries

Abstract: Recent interest in protein intake per meal is observed in studies that have reported the protein intake patterns in different countries; however, comparisons of these data are lacking. We aimed to compare protein intake patterns and the percentage of inadequate protein intake (IPI) per day and meal in older adults from different countries. We acquired data of protein intake in older adults from four countries (Mexico, United States of America, Germany, and United Kingdom). We compared protein intake (per day a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…However, these reports focused on daily protein intake, and few studies have examined intake at each meal. In addition, studies that have investigated protein intake in each diet have only investigated intake and have not confirmed the characteristics with respect to the distribution of intake [ 36 ]. Therefore, the finding that breakfast and lunch protein intakes are particularly related to physical activity is a new finding first presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, these reports focused on daily protein intake, and few studies have examined intake at each meal. In addition, studies that have investigated protein intake in each diet have only investigated intake and have not confirmed the characteristics with respect to the distribution of intake [ 36 ]. Therefore, the finding that breakfast and lunch protein intakes are particularly related to physical activity is a new finding first presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Protein is known to be one of the most important nutrients for older adults with low intakes been associated with higher losses of lean mass ( 19 ). Many researchers suggested that daily protein intake above the recommended dietary allowance (RDA) of 0.8 g/kg/d might be associated with higher physical performance, maintenance and increased muscle mass and decreased risk of physical disability ( 45 ). Therefore, a higher recommended protein intake of 1.0 g/kg/d–1.2 g/kg/d was recently proposed for healthy maintenance of muscle and up to 1.2 g/kg/d–1.5 g/kg/d for older adults with acute or chronic diseases ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Snacks in our sample, as in other institutionalized [ 21 ] and community-dwelling older adults [ 19 , 20 ], were mainly dairy products and pastry. Overall, the differences in protein sources between studies and settings can be considered marginal, especially when taking individual, regional and country-specific dietary habits into account [ 1 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many older adults, protein intake is below recommended amounts [ 1 ], but adequate intake is crucial for maintaining muscle mass and function [ 2 , 3 ]. Additionally, in older age, protein requirements appear to be higher due to a high prevalence of inflammation, wounds, infections, critical illness [ 4 , 5 , 6 ] and reduced anabolic response after protein ingestion [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation